Academic surgery amid the COVID-19 pandemic: A perspective of the present and future challenges. (August 2022) - Zheng, MinHua; Boni, Luigi; Uranues, Selman; Chen, William Tzu-Liang; Fingerhut, Abraham
Abstract: This narrative review describes the trials and tribulations of academic surgeons in four major cities of their respective countries and the solutions they retained to keep academia alive in their practice. The four pillars of an "academic surgeon" _teaching, producing scientific works presented in meetings, publications and research_ are dealt with bearing in mind the modifications brought about by the pandemic and the solutions to keep academia active. Throughout the pandemic, the ultimate goal has been and will be to improve care and train the next generation of surgeons and encourage and monitor researchers, guide the mentees through the tasks of leadership, and foster good sound presentations at scientific meetings and encourage innovative and fruitful publications. The pros and cons of the alternatives imposed by the pandemic for the above-mentioned academic components, based on the literature, are reviewed and analyzed as they are taking place today in Shanghai, Milan, Graz, TaiChung and Hsinchu. Our perspective for the future is that teaching will take a new aspect and make wide use of electronic platforms, but also, the face-to-face modality will surface again. According to local needs and funding, many will most likely choose the hybrid solution (electronic and presential). Production of scientific works in meetings has gained momentum, again with the hybrid solution being preferred. Scientific publications have already increased on topics that are no longer related to COVID-19, and both clinical and experimental research are flourishing. This review can provide insight to guide young and accomplished academic surgeons through these difficult times and beyond, promoting a renaissance of clinical research and relevant publications, teaching of surgery and scientific meetings with a hybrid approach, and, finally, contribute to the training and formation of a new generation of surgeons for the future post-COVID-19 era.